A case of non-puerperal uterine inversion in reproductive age - Dinku, Getu (Ethiopian Journal of Reproductive Health, 2020)
Non- puerperal uterine inversion is a rare clinical condition which most often occurs with tumor implanted of the fundus of the uterus. Leiomyoma is the commonest cause as a leading point for non-puerperal uterine inversion to occur. Unusual case report of non-puerperal uterine inversion caused by sub mucous leiomyoma is reported to 38 years old para 5 presented with vaginal bleeding and protruding mass per vagina with anemia and offensive discharge. Uterine inversion was corrected abdominally by Haultain's procedure after vaginal myomectomy followed by abdominal hysterectomy. Both the ovaries were conserved. Key words : uterine inversion, non-puerperal , leiomyoma